Chromatin modifications during repair of environmental exposure‐induced DNA damage: A potential mechanism for stable epigenetic alterations. (20th November 2013) - O'Hagan, Heather M.; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Exposures to environmental toxicants and toxins cause epigenetic changes that likely play a role in the development of diseases associated with exposure. The mechanism behind these exposure‐induced epigenetic changes is currently unknown. One commonality between most environmental exposures is that they cause DNA damage either directly or through causing an increase in reactive oxygen species, which can damage DNA. Like transcription, DNA damage repair must occur in the context of chromatin requiring both histone modifications and ATP‐dependent chromatin remodeling. These chromatin changes aid in DNA damage accessibility and signaling. Several proteins and complexes involved in epigenetic silencing during both development and cancer have been found to be localized to sites of DNA damage. The chromatin‐based response to DNA damage is considered a transient event, with chromatin being restored to normal as DNA damage repair is completed. However, in individuals chronically exposed to environmental toxicants or with chronic inflammatory disease, repeated DNA damage‐induced chromatin rearrangement may ultimately lead to permanent epigenetic alterations. Understanding the mechanism behind exposure‐induced epigenetic changes will allow us to develop strategies to prevent or reverse these changes. This review focuses on epigenetic changes and DNA damage induced by environmental exposures, the chromatin changes that occur around sites of DNA damage, and how these transient chromatin changes may lead to heritable epigenetic alterations at sites of chronic exposure. Environ. Mol. Mutagen. 55:278–291, 2014. © 2013 Wiley Periodicals, Inc.